EP 55. Perception of the Double-Flash-Illusion in patients with Parkinson's disease and its modulation by dopamine compared to matched healthy controls. Issue 9 (September 2016) - Pundmann, V.; Brenner, M.; Schnitzler, A.; Ferrea, S.; Südmeyer, M.; Lange, J.
Abstract : When a brief single visual stimulus is presented interposed between two brief tactile stimuli in a time window (SOA; Stimulus Onset Asynchrony) of 70–100 ms healthy subjects frequently perceive an illusory second visual stimulus. This phenomenon is known as "Double-Flash-Illusion" (DFI) (Shams et al., 2000 ). Hypothesis: Studies have shown that patients with Parkinson's disease (PD) need a longer time interval to perceive two unimodal stimuli correctly as two (Artieda et al., 1992 ). Here we investigated whether in PD patients the time window to perceive the DFI is also prolonged compared to healthy controls. We hypothesized that the SOA to perceive the DFI is prolonged in PD patients and that dopamine medication (ON) shortens the SOA to perceive the DFI relative to medication withdrawal (OFF). Methods: Up to now 20 PD patients (6 female; mean age 58, 5 y) and 16 matched controls took part. Only patients with a hypokinetc-rigid subtype in state I–III by Hoehn & Yahr, who received medical treatment only and did not have any other neurological disorders took part. Participants received visuo-electrotactile stimulation to the left index finger. Either one or two visual stimuli were presented with either one or two electrotactile stimuli (combinations: v, vv, tv, tvt, tvtv, vtv; with v standing for the visual and t for the tactile stimulus). The stimuli in each combination were separated by the following SOAs: 67, 84, 100, 135, 170, 200, 270, 300, 400, 500 and 600 ms. The condition with two electrotactile stimuli interposed with one visual stimulus (tvt) was supposed to induce the DFI. Participants reported the number of perceived visual stimuli. The experiment was first done without medication (OFF) and than repeated with dopamine medication (ON) with PD patients. The control subjects performed the experiment twice without any medication. The UPDRS (Unified Parkinson's Disease Rating Score) was measured in OFF and ON for the PD group. Findings: Among the PD patients, we found two groups: one group (9 subjects) who did not report the DFI (NOSEEer; one female), while the other group (11 subjects) frequently reported the DFI (SEEer; 5 female). The SEEer-Group shows significantly increased DFI perception in the ON condition compared to OFF for the SOAs 64, 100 and 135 ms. Additionally, we found that the SOA for which we observed maximum illusory perception shifted from 270 ms to 200 ms from OFF to ON. In the control group we found 12 SEEer and 4 NOSEEer. There was no significant difference between first measurements in PD patients (OFF) and controls with respect to perception of illusion. When patients' ON condition was compared to the controls' second measurement the patients perceived the stimulation significantly more often as two visual stimuli for the SOAs 64 and 84 ms. Conclusion: In summary, we find a modulation of DFI perception by dopamine: With medication, patients perceived the illusion more often for short SOAs than without medication. Interestingly, we did not find a significant difference between patients in the OFF state and healthy controls' first measurement. This finding indicates that other factors than disease or dopamine may additionally influence the perception of the DFI. Future studies analysing brain activity of both groups might help to understand the present findings as well as the differences between SEEer group and NOSEEer group.